Beeinflussung der Wirkung von Ernährungsinformation durch Framing: Analyse am Beispiel von Folsäure; Influencing the Effect of Nutritional Information by Framing: Analysis using the Example of Folic Acid - Kathrin Lensch; Monika Hartmann; Johannes Simons (German Journal of Agricultural Economics (GJAE), 2011)
– One way to support consumers in integrating health aspects into their purchase and eating behaviour is to make information available to consumers in a comprehensible manner. In behavioural economics framing effects are acknowledged as important factors influencing perception of information. In this paper framing effects are analysed by means of an experiment using the example of information about folic acid. The results give evidence that framing influences consumers' perception, the need for information and decision process even though the effect is small. Overall, a negative frame results in a stronger effect than a positive one.
Keywords: 330; Konsumentenverhalten; Produktinformation; Prospect Theory; Verhaltensökonomik; Experiment